Preparation method of porous carbon nanofiber wave-absorbing material containing nitrogen-coordinated cobalt structure

CN122959925APending Publication Date: 2026-10-23NANCHANG HANGKONG UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611410718.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]针对上述现状,本发明的目的在于解决现有钴基磁碳吸波材料在热处理过程中含钴组分易发生聚集、微观结构难以有效调控以及介电损耗与磁损耗匹配不足的问题,提供一种含氮配位钴结构的多孔碳纳米纤维吸波材料及其制备方法,通过Zn/Co-ZIFs前驱体与静电纺丝相结合,在三维多孔碳纳米纤维网络中构建分散的含钴组分及Co-N配位结构,以改善材料的阻抗匹配和电磁波衰减性能

Benefits of technology

1、制备与结构调控:采用Zn/Co-ZIFs作为含钴前驱体,并通过静电纺丝使其预先分散于聚合物纳米纤维中,经预氧化和碳化后形成三维多孔碳纳米纤维网络,Co纳米颗粒分散并嵌入于碳纳米纤维中,有利于限制含钴组分在高温处理过程中的迁移和聚集,并使含钴组分分散于碳纳米纤维内部;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959925A_ABST
    Figure CN122959925A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a porous carbon nanofiber wave-absorbing material containing a nitrogen-coordinated cobalt structure, which comprises the following steps: dispersing a prepared Zn / Co-ZIFs precursor in a spinning solution containing polyacrylonitrile, obtaining a Zn / Co-ZIFs / polymer composite nanofiber precursor film through electrospinning, and forming a three-dimensional porous carbon nanofiber network through pre-oxidation and carbonization to obtain the porous carbon nanofiber wave-absorbing material containing the nitrogen-coordinated cobalt structure. The wave-absorbing material contains Co-N coordination structures and dispersed Co nanoparticles, can synergistically control dielectric loss, magnetic loss and impedance matching, the minimum reflection loss can reach-54.7 dB at a filling ratio of 20 wt%, the effective absorption bandwidth can reach 6.68 GHz, and the wave-absorbing material can be applied to the fields of electromagnetic wave absorption, radar cross section reduction and electromagnetic protection of electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt-containing structure, specifically belonging to the field of microwave absorbing material technology. Background Technology

[0002] With the rapid development of wireless communication, electronic devices, and radar technology, electromagnetic radiation and electromagnetic interference problems are becoming increasingly prominent, placing higher demands on electromagnetic wave absorbing materials that possess characteristics such as light weight, thin thickness, strong absorption, and wide effective absorption bandwidth. In existing technologies, the composite of magnetic metals and carbon materials is an important technical approach to improve the electromagnetic loss capability of absorbing materials. Among these, the "Preparation Method of Cobalt-Nickel Alloy@Nitrogen-Doped Porous Carbon Composite Microwave Absorbing Material" (CN202011289216.6) achieves strong electromagnetic wave attenuation capability through the composite of CoNi alloy and nitrogen-containing porous carbon; the "Preparation and Microwave Absorption Performance Study of Cobalt-Based Zeolite Imidazole Ester Framework-Derived Magnetic Carbon Composite Material" uses the pyrolysis of CoZn-ZIF precursor to prepare Co / CoO / C composite materials. While the absorbing materials prepared above can achieve good absorption performance, the magnetic metal components are prone to migration and aggregation during heat treatment, easily forming large metal particles or clusters, thus affecting the internal electromagnetic parameter distribution, impedance matching, and broadband absorption performance of the material.

[0003] Porous carbon nanofibers possess characteristics such as low density, high specific surface area, continuous conductive network, and abundant interfaces, which are beneficial for electromagnetic waves to undergo multiple reflections, scattering, and conduction losses within the material. Simultaneously, the MNC coordination structure formed by metal and nitrogen can alter the local electronic structure and promote the redistribution of interfacial charges, thereby enhancing dipole polarization and interfacial polarization.

[0004] Achieving effective dispersion of cobalt-containing components within porous carbon nanofiber networks, while simultaneously constructing Co-N coordination structures and improving impedance matching through the synergistic effect of porous structure, dielectric loss, and magnetic loss, is a key technical challenge for further enhancing the broadband electromagnetic wave absorption performance of cobalt-based carbon materials. This invention combines Zn / Co-ZIFs precursors with electrospinning technology, pre-dispersing the cobalt-containing precursors within polymer nanofibers. A three-dimensional porous carbon nanofiber network containing Co-N coordination structures and Co nanoparticles is then constructed through pre-oxidation and carbonization processes. Summary of the Invention

[0005] In view of the above-mentioned situation, the purpose of this invention is to solve the problems of cobalt-containing components easily agglomerating during heat treatment, difficulty in effectively controlling the microstructure, and insufficient matching of dielectric loss and magnetic loss in existing cobalt-based magnetic carbon absorbing materials. The invention provides a porous carbon nanofiber absorbing material with nitrogen-coordinated cobalt structure and its preparation method. By combining Zn / Co-ZIFs precursor with electrospinning, a dispersed cobalt-containing component and Co-N coordination structure are constructed in a three-dimensional porous carbon nanofiber network to improve the impedance matching and electromagnetic wave attenuation performance of the material.

[0006] This invention discloses a method for preparing a nitrogen-cobalt-coated porous carbon nanofiber microwave absorbing material. This method combines a Zn / Co-ZIFs precursor with electrospinning to construct a dispersed cobalt-containing component and a Co-N coordination structure within a three-dimensional porous carbon nanofiber network, thereby obtaining a nitrogen-cobalt-coated porous carbon nanofiber microwave absorbing material. The specific steps are as follows: Step 1: Preparation of Zn / Co-ZIFs precursor Polyoxyethylene-polyoxypropylene ether-polyoxyethylene triblock copolymer (F127) was dissolved in methanol, and zinc nitrate hexahydrate and cobalt nitrate hexahydrate (II) were dissolved in methanol. After mixing evenly, a methanol solution of 2-methylimidazole was added. After reaction, the mixture was separated, washed and dried to obtain the Zn / Co-ZIFs precursor. Step 2: Preparation of precursor solution Polyacrylonitrile and polyvinylpyrrolidone were added to an N,N-dimethylformamide solution and stirred at room temperature for 11-13 hours to form a uniformly dispersed polymer solution. Then, a Zn / Co-ZIFs precursor was added and the solution was sonicated for 1-2 hours to obtain a precursor solution. Step 3: Preparation of Zn / Co-ZIFs / polymer composite nanofiber precursor membrane The precursor solution was electrospun to obtain a Zn / Co-ZIFs / polymer composite nanofiber precursor membrane. Step 4: Preparation of porous carbon nanofiber microwave absorbing material with nitrogen-cobalt coordination structure The Zn / Co-ZIFs / polymer composite nanofiber precursor film was pre-oxidized in air and then carbonized in nitrogen to obtain a porous carbon nanofiber microwave absorbing material with nitrogen-coordinated cobalt structure.

[0007] In step 1, the material ratio of F127 to methanol is 1 g: 48-52 mL; the material ratio of the total mass of zinc nitrate hexahydrate and cobalt(II) nitrate hexahydrate to the volume of methanol is 3.80-3.88 g: 48-52 mL; the molar ratio of zinc nitrate hexahydrate to cobalt(II) nitrate hexahydrate is 8.9-9.1:4; the material ratio of 2-methylimidazole to methanol is 3.2 g: 96-104 mL; the mass ratio of F127 to 2-methylimidazole is 1: 3.1-3.3; and the ratio of the total molar amount of zinc nitrate hexahydrate and cobalt(II) nitrate hexahydrate to the molar amount of 2-methylimidazole is 1: 2.98-3.02.

[0008] In step 2, the average molecular weight of polyacrylonitrile is 150,000; the mass ratio of the polymer to the Zn / Co-ZIFs precursor is 5:4; the material ratio of the total polymer mass to N,N-dimethylformamide is 0.5 g: 6-7 mL; and the mass ratio of polyacrylonitrile to polyvinylpyrrolidone is 4:1.

[0009] In step 3, the positive voltage of electrospinning is 9.5–10.5 kV, the negative voltage is -0.5–0 kV, and the precursor solution propulsion rate is 0.018–0.022 mL·min. -1 The distance between the spinning needle and the collector is 12–15 cm.

[0010] In step 4, the pre-oxidation treatment temperature is 280 ℃, the holding time is 1–1.5 h, and the heating rate is 4–5 ℃·min. -1 Carbonization temperature: 700–900 ℃; holding time: 2–3 h; heating rate: 4–5 ℃·min. -1 .

[0011] The beneficial effects of this invention are: 1. Preparation and structure control: Zn / Co-ZIFs were used as cobalt-containing precursors and pre-dispersed in polymer nanofibers by electrospinning. After pre-oxidation and carbonization, a three-dimensional porous carbon nanofiber network was formed. Co nanoparticles were dispersed and embedded in the carbon nanofibers, which helped to limit the migration and aggregation of cobalt-containing components during high-temperature treatment and to disperse the cobalt-containing components inside the carbon nanofibers. 2. Synergistic Electromagnetic Loss: The Co-N coordination structure, Co nanoparticles, and continuous carbon nanofiber network jointly participate in electromagnetic wave attenuation. The porous carbon nanofiber network can increase the electromagnetic wave propagation path and provide a channel for conduction loss; the localized non-uniform charge distribution formed by the Co-N coordination structure is conducive to enhancing dipole polarization and interface polarization; Co nanoparticles can provide magnetic response, thereby achieving synergistic control of dielectric loss and magnetic loss; 3. Broadband absorption performance: Under the condition that the absorbing material filling mass fraction is 20 wt.%, the obtained CNPF-1 achieves a minimum reflection loss of -54.7 dB with a matching thickness of 3.1 mm and an effective absorption bandwidth of 6.34 GHz with a thickness of 2.3 mm; CNPF-3 achieves an effective absorption bandwidth of 6.68 GHz with a thickness of 2.2 mm. 4. Radar scattering attenuation potential: Under the set simulation conditions, CNPF-1 in Example 1 can achieve a maximum RCS reduction of 12.85 dB·m², which can be applied to electromagnetic wave absorption, radar cross section reduction and electromagnetic protection of electronic devices. Attached Figure Description

[0012] Figure 1 The X-ray diffraction patterns of the products obtained in Examples 1, 2, and 3 of this invention are shown below. Figure 2 This is a scanning electron microscope image of CNPF-1 prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of CNPF-2 prepared in Example 2 of the present invention; Figure 4 This is a scanning electron microscope image of CNPF-3 prepared in Example 3 of the present invention; Figure 5 This is a graph showing the electromagnetic reflection loss data of CNPF-1 in Embodiment 1 of the present invention; Figure 6 This is a graph showing the electromagnetic reflection loss data of CNPF-2 in Embodiment 2 of the present invention; Figure 7 This is a graph showing the electromagnetic reflection loss data of CNPF-3 in Embodiment 3 of the present invention; Figure 8 This is a diagram showing the effective absorption bandwidth of CNPF-1 at different thicknesses in Embodiment 1 of the present invention; Figure 9 This is a diagram showing the effective absorption bandwidth of CNPF-2 at different thicknesses in Embodiment 2 of the present invention; Figure 10 This is a diagram showing the effective absorption bandwidth of CNPF-3 at different thicknesses in Embodiment 3 of the present invention. Figure 11 This is a schematic diagram of the RCS reference model calculation of the present invention; Figure 12 This is a graph showing the reduction in RCS values ​​in Embodiment 1 of the present invention; Figure 13 This is a three-dimensional diagram of the RCS in Embodiment 1 of the present invention; Figure 14 This is a graph showing the reduction in RCS values ​​in Embodiment 2 of the present invention; Figure 15This is a graph showing the reduction in RCS value in Embodiment 3 of the present invention. Detailed Implementation

[0013] Example 1 Preparation process of porous carbon nanofiber microwave absorbing material with nitrogen-cobalt coordination structure (CNPF-1): Step 1: Dissolve 1 g of polyoxyethylene-polyoxypropylene ether-polyoxyethylene triblock copolymer (F127) in 50 mL of methanol solution to form a clear solution; then mix with 50 mL of methanol solution containing 2.68 g of zinc nitrate hexahydrate and 1.16 g of cobalt(II) nitrate hexahydrate, and stir at room temperature for 5 minutes. Then, inject 100 mL of methanol solution containing 3.2 g of 2-methylimidazole into the above solution; after stirring at 60 °C for 30 minutes in the reflux system, a purple crystalline precipitate is obtained. After natural cooling, collect it in a centrifuge tube and wash it three times with anhydrous ethanol. After drying in a vacuum oven at 60 °C for 12 h, a purple solid powder is obtained, denoted as Zn / Co-ZIFs precursor; Step 2: Add 500 mg of polyacrylonitrile to 6.5 mL of N,N-dimethylformamide solution and stir at room temperature for 12 h to form a uniformly dispersed polymer solution; then add 400 mg of Zn / Co-ZIFs precursor to the above polymer solution, sonicate for 1 h, and stir for 2 h until Zn / Co-ZIFs are uniformly dispersed to obtain a precursor solution. Step 3: Transfer the precursor solution into a syringe equipped with an 18-gauge needle; perform electrospinning using an electrospinning device, with the positive / negative voltage, syringe advance rate, and distance between the needle and the collector set to +10 kV / -0.5 kV and 0.02 mL·min, respectively. -1 14 cm; simultaneously, using silicone paper as a collector, the formed purple Zn / Co-ZIFs / polymer composite nanofiber precursor film was collected, and the obtained film was dried in a vacuum oven at 60 °C for 12 h; Step 4: Cut the Zn / Co-ZIFs / polymer composite nanofiber precursor film into 100 mm × 30 mm sheets, sandwich them in a 100 mm × 30 mm × 2 mm carbon plate, and pre-oxidize them in air at 280 ℃ for 1 h with a heating rate of 5 ℃·min. -1 Then, after introducing nitrogen, carbonization was carried out at 800 °C for 2 h with a heating rate of 5 °C / min. -1 The porous carbon nanofiber microwave absorbing material with nitrogen-cobalt coordination structure (named CNPF-1) was obtained by purging nitrogen atmosphere and waiting for the temperature to drop to room temperature. Step 5: CNPF-1 is mixed with molten paraffin (mass ratio of absorbing material to paraffin is 1:4) and formed into a ring, wherein the absorbing material accounts for 20 wt.% of the total mass of the ring. The electromagnetic parameters of this material are measured using a vector network analyzer. According to transmission line theory, the reflection loss of the material to electromagnetic waves is calculated using the following equation: ; in, Z 0 represents the characteristic impedance of air. f For frequency, d For sample thickness, c At the speed of light, ε r and μ r These are the complex permittivity and complex permeability, respectively; when RL When the value is ≤-10 dB, the corresponding frequency range is defined as the effective absorption bandwidth (EAB). Step 6: The radar scattering characteristics of CNPF-1 were simulated using CST electromagnetic field simulation software. The RCS value of CNPF-1 was simulated under open boundary conditions using CST. The length and width of each layer were set to 90 mm, and the thicknesses of the PEC and absorbing layers were set to 1 mm and 4 mm, respectively. The PEC layer was also used as a reference for RCS reduction. Subsequently, the absorbing model was placed on the XOY plane, with microwaves incident along the Z-axis. Furthermore, the far-field monitoring frequency was set to 8.90 GHz. The reduction in radar cross-section was calculated using the following formula: ; Where S is the area of ​​the simulated absorption model, λ is the wavelength of the incident electromagnetic wave, Es is the electric field strength of the emitted wave, and Ei is the electric field strength of the received wave.

[0014] Example 2 Preparation process of porous carbon nanofiber microwave absorbing material (CNPF-2) with nitrogen-cobalt coordination structure: Step 1: Dissolve 1 g of polyoxyethylene-polyoxypropylene ether-polyoxyethylene triblock copolymer (F127) in 50 mL of methanol solution to form a clear solution; then mix with 50 mL of methanol solution containing 2.68 g of zinc nitrate hexahydrate and 1.16 g of cobalt(II) nitrate hexahydrate, and stir at room temperature for 5 minutes. Then, inject 100 mL of methanol solution containing 3.2 g of 2-methylimidazole into the above solution; after stirring at 60 °C for 30 minutes in the reflux system, a purple crystalline precipitate is obtained. After natural cooling, collect the sample in a centrifuge tube and wash it three times with fresh anhydrous ethanol. After drying in a vacuum oven at 60 °C for 12 h, a purple solid powder is obtained, denoted as Zn / Co-ZIFs. Step 2: Add 400 mg of polyacrylonitrile and 100 mg of polyvinylpyrrolidone to 6.5 mL of N,N-dimethylformamide solution and stir at room temperature for 12 h to form a uniformly dispersed polymer solution; then add 400 mg of Zn / Co-ZIFs prepared in Step 1 to the above polymer solution, sonicate for 1 h, and stir for 2 h until Zn / Co-ZIFs are uniformly dispersed to obtain the precursor solution. If the solution is too thick, add additional N,N-dimethylformamide; Step 3: Transfer the precursor solution prepared in Step 2 into a syringe equipped with an 18-gauge needle; perform electrospinning using an electrospinning device, with the positive / negative voltage, syringe advance rate, and distance between the needle and the collector set to +10.5 kV / -0.5 kV and 0.02 mL·min, respectively. -1 14 cm; at the same time, silicone paper was used as a collector to collect the formed purple Zn / Co-ZIFs / polymer composite nanofiber precursor film, and the obtained film was dried in a vacuum oven at 60 °C for 12 h; Step 4: The Zn / Co-ZIFs / polymer composite nanofiber precursor film prepared in Step 3 was cut into 100 mm × 30 mm sheets, sandwiched between 100 mm × 30 mm × 2 mm carbon plates, and pre-oxidized in air at 280 ℃ for 1 h with a heating rate of 5 ℃·min. -1 Then, after introducing nitrogen, carbonization was carried out at 800 °C for 2 h with a heating rate of 5 °C / min. -1 Then, by introducing a nitrogen atmosphere and waiting for the temperature to drop to room temperature, a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt coordination structure (named CNPF-2) can be obtained. Step 5: The CNPF-2 prepared in Step 4 is mixed with molten paraffin (mass ratio of absorbing material to paraffin is 1:4) and formed into a ring, wherein the absorbing material accounts for 20 wt.% of the total mass of the ring. The electromagnetic parameters of this material are measured using a vector network analyzer. According to transmission line theory, the reflection loss of the material to electromagnetic waves is calculated using the following equation: ; in, Z 0 represents the characteristic impedance of air. f For frequency, d For sample thickness, c At the speed of light, ε r and μ r These are the complex permittivity and complex permeability, respectively; when RL When the value is ≤-10 dB, the corresponding frequency range is defined as the effective absorption bandwidth (EAB). Step 6: The radar scattering characteristics of CNPF-2 were simulated using CST electromagnetic field simulation software. The RCS value of CNPF-2 was simulated under open boundary conditions using CST. The length and width of each layer were set to 90 mm, and the thicknesses of the PEC and absorbing layers were set to 1 mm and 4 mm, respectively. The PEC layer was also used as a reference for RCS reduction. Subsequently, the absorbing model was placed on the XOY plane, with microwaves incident along the Z-axis. Furthermore, the far-field monitoring frequency was set to 14.26 GHz. The reduction in radar cross-section was calculated using the following formula: ; Where S is the area of ​​the simulated absorption model, λ is the wavelength of the incident electromagnetic wave, Es is the electric field strength of the emitted wave, and Ei is the electric field strength of the received wave.

[0015] Example 3 Preparation process of porous carbon nanofiber microwave absorbing material with nitrogen-cobalt coordination structure (CNPF-3): Step 1: Dissolve 1 g of polyoxyethylene-polyoxypropylene ether-polyoxyethylene triblock copolymer (F127) in 50 mL of methanol solution to form a clear solution; then mix with 50 mL of methanol solution containing 2.68 g of zinc nitrate hexahydrate and 1.16 g of cobalt(II) nitrate hexahydrate, and stir at room temperature for 5 minutes. Then, inject 100 mL of methanol solution containing 3.2 g of 2-methylimidazole into the above solution; after stirring at 60 °C for 30 minutes in the reflux system, a purple crystalline precipitate is obtained. After natural cooling, collect the sample in a centrifuge tube and wash it three times with fresh anhydrous ethanol. After drying in a vacuum oven at 60 °C for 12 h, a purple solid powder is obtained, denoted as Zn / Co-ZIFs precursor; Step 2: Add 300 mg of polyacrylonitrile and 200 mg of polyvinylpyrrolidone to 6.5 mL of N,N-dimethylformamide solution and stir at room temperature for 12 h to form a uniformly dispersed polymer solution; then add 400 mg of the Zn / Co-ZIFs precursor prepared in Step 1 to the above polymer solution, sonicate for 1 h, and stir for 2 h until the Zn / Co-ZIFs precursor is uniformly dispersed to obtain a precursor solution. If the solution is too thick, add additional N,N-dimethylformamide; Step 3: Transfer the precursor solution prepared in Step 2 into a syringe equipped with an 18-gauge needle; perform electrospinning using an electrospinning device, with the positive / negative voltage, syringe advance rate, and distance between the needle and the collector set to +10 kV / -0.5 kV and 0.02 mL·min, respectively. -114 cm; at the same time, silicone paper was used as a collector to collect the formed purple Zn / Co-ZIFs / polymer composite nanofiber precursor film, and the obtained film was dried in a vacuum oven at 60 °C for 12 h; Step 4: The Zn / Co-ZIFs / polymer composite nanofiber precursor film prepared in Step 3 was cut into 100 mm × 30 mm sheets, sandwiched between 100 mm × 30 mm × 2 mm carbon plates, and pre-oxidized in air at 280 ℃ for 1 h with a heating rate of 5 ℃·min. -1 Then, after introducing nitrogen, carbonization was carried out at 800 °C for 2 h with a heating rate of 5 °C / min. -1 Then, by introducing a nitrogen atmosphere and waiting for the temperature to drop to room temperature, a porous carbon nanofiber absorbing material with a nitrogen-cobalt coordination structure (named CNPF-3) can be obtained. Step 5: The CNPF-3 prepared in Step 4 is mixed with molten paraffin (mass ratio of absorbing material to paraffin is 1:4) and formed into a ring, wherein the absorbing material accounts for 20 wt.% of the total mass of the ring. The electromagnetic parameters of this material are measured using a vector network analyzer. According to transmission line theory, the reflection loss of the material to electromagnetic waves is calculated using the following equation: ; in, Z 0 represents the characteristic impedance of air. f For frequency, d For sample thickness, c At the speed of light, ε r and μ r These are the complex permittivity and complex permeability, respectively; when RL When the value is ≤-10 dB, the corresponding frequency range is defined as the effective absorption bandwidth (EAB). Step 6: The radar scattering characteristics of CNPF-3 were simulated using CST electromagnetic field simulation software. The RCS value of CNPF-3 was simulated under open boundary conditions using CST. The length and width of each layer were set to 90 mm, and the thicknesses of the PEC and absorbing layers were set to 1 mm and 4 mm, respectively. The PEC layer was also used as a reference for RCS reduction. Subsequently, the absorbing model was placed on the XOY plane, with microwaves incident along the Z-axis. Furthermore, the far-field monitoring frequency was set to 8.48 GHz. The reduction in radar cross-section was calculated using the following formula: ; Where S is the area of ​​the simulated absorption model, λ is the wavelength of the incident electromagnetic wave, Es is the electric field strength of the emitted wave, and Ei is the electric field strength of the received wave.

[0016] Figure 1 The X-ray diffraction patterns of the products obtained in step 4 of Examples 1, 2, and 3 are shown. CNPF-1 prepared in Example 1 shows a diffraction peak at 44.3°, which can be attributed to the (111) crystal plane of metallic Co, indicating that there is a metallic Co crystal phase in CNPF-1. The samples obtained in Examples 1 and 2 show a broad peak at about 23.5°, which can be attributed to the (002) crystal plane of graphitized carbon.

[0017] Figure 2 The image shows a scanning electron microscope image of CNPF-1 prepared in Example 1. A clear three-dimensional porous network structure can be seen in the image, and pore structures can be observed on the surface of the particles and fibers.

[0018] Figure 3 The image shows a scanning electron microscope image of CNPF-2 prepared in Example 2. A relatively clear three-dimensional porous network structure can be seen in the image, and a large number of large pores can be observed on the surface.

[0019] Figure 4 The image shows a scanning electron microscope image of CNPF-3 prepared in Example 3. A relatively obvious three-dimensional porous network structure can be seen in the image. Large pores can be observed on the surface, and some fibers are broken, indicating that the integrity of the fiber network of this sample has been reduced.

[0020] Figure 5 The image shows the electromagnetic reflection loss data of CNPF-1 calculated in step 5 of Example 1. When the mass filler ratio is 20 wt.%, the minimum reflection loss of CNPF-1 can reach −54.7 dB, corresponding to a matching thickness of 3.1 mm.

[0021] Figure 6 The image shows the electromagnetic reflection loss data of CNPF-2 calculated in step 5 of Example 2. When the mass filler ratio is 20 wt.%, the minimum reflection loss of CNPF-2 can reach −17.44 dB, corresponding to a matching thickness of 1.8 mm.

[0022] Figure 7 The image shows the electromagnetic reflection loss data of CNPF-3 calculated in step 5 of Example 3. When the mass filler ratio is 20 wt.%, the minimum reflection loss of CNPF-3 can reach −40.86 dB, corresponding to a matching thickness of 3.0 mm.

[0023] Figure 8 The effective absorption bandwidth diagram of CNPF-1 prepared in Example 1 at different thicknesses is shown. The effective absorption bandwidth of CNPF-1 reaches 6.34 GHz when the thickness is 2.3 mm.

[0024] Figure 9The effective absorption bandwidth diagram of CNPF-2 prepared in Example 2 at different thicknesses is shown. The effective absorption bandwidth of CNPF-2 reaches 5.24 GHz when the thickness is 2.0 mm.

[0025] Figure 10 The effective absorption bandwidth of CNPF-3 prepared in Example 3 at different thicknesses is shown in the figure. The effective absorption bandwidth of CNPF-3 reaches 6.68 GHz when the thickness is 2.2 mm.

[0026] Figure 11 This is a schematic diagram of the RCS reference model calculation. Figure 12 This is a graph showing the RCS reduction of CNPF-1 calculated in step 6 of Example 1. Figure 13 The image shows the three-dimensional RCS of CNPF-1. Under the set simulation conditions, the maximum RCS reduction of CNPF-1 at 0° incidence is 12.85 dB·m², indicating that this material has the potential for radar electromagnetic wave attenuation applications.

[0027] Figure 14 The graph shows the RCS reduction of CNPF-2 calculated in step 6 of Example 2. Under the set simulation conditions, its maximum RCS reduction is 4.87 dB·m².

[0028] Figure 15 The graph shows the RCS reduction of CNPF-3 calculated in step 6 of Example 3. Under the set simulation conditions, its maximum RCS reduction is 7.23 dB·m².

Claims

1. A method for preparing a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt-coordinated structure, characterized in that: The preparation method described above utilizes a combination of Zn / Co-ZIFs precursors and electrospinning to construct dispersed cobalt-containing components and Co-N coordination structures within a three-dimensional porous carbon nanofiber network, thereby obtaining a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt coordination structure. The specific steps are as follows: Step 1: Preparation of Zn / Co-ZIFs precursor Polyoxyethylene-polyoxypropylene ether-polyoxyethylene triblock copolymer was dissolved in methanol, and zinc nitrate hexahydrate and cobalt nitrate hexahydrate (II) were dissolved in methanol. After mixing evenly, a methanol solution of 2-methylimidazole was added. After reaction, the mixture was separated, washed and dried to obtain the Zn / Co-ZIFs precursor. Step 2: Preparation of precursor solution Polyacrylonitrile and polyvinylpyrrolidone were added to an N,N-dimethylformamide solution and stirred at room temperature for 11-13 hours to form a uniformly dispersed polymer solution. Then, a Zn / Co-ZIFs precursor was added and the solution was sonicated for 1-2 hours to obtain a precursor solution. Step 3: Preparation of Zn / Co-ZIFs / polymer composite nanofiber precursor membrane The precursor solution was electrospun to obtain a Zn / Co-ZIFs / polymer composite nanofiber precursor membrane. Step 4: Preparation of porous carbon nanofiber microwave absorbing material with nitrogen-cobalt coordination structure The Zn / Co-ZIFs / polymer composite nanofiber precursor film was pre-oxidized in air and then carbonized in nitrogen to obtain a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt-coordinated structure.

2. The method for preparing a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt-coordinated structure according to claim 1, characterized in that: In step 1, the material ratio of F127 to methanol is 1 g: 48-52 mL; the material ratio of the total mass of zinc nitrate hexahydrate and cobalt(II) nitrate hexahydrate to the volume of methanol is 3.80-3.88 g: 48-52 mL; the molar ratio of zinc nitrate hexahydrate to cobalt(II) nitrate hexahydrate is 8.9-9.1:4; the material ratio of 2-methylimidazole to methanol is 3.2 g: 96-104 mL; the mass ratio of F127 to 2-methylimidazole is 1: 3.1-3.3; and the ratio of the total molar amount of zinc nitrate hexahydrate and cobalt(II) nitrate hexahydrate to the molar amount of 2-methylimidazole is 1: 2.98-3.

02.

3. The method for preparing a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt-coordinated structure according to claim 1, characterized in that: In step 2, the average molecular weight of polyacrylonitrile is 150,000; the mass ratio of the polymer to the Zn / Co-ZIFs precursor is 5:4; the material ratio of the total polymer mass to N,N-dimethylformamide is 0.5 g: 6-7 mL; and the mass ratio of polyacrylonitrile to polyvinylpyrrolidone is 4:

1.

4. The method for preparing a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt-coordinated structure according to claim 1, characterized in that: In step 3, the positive voltage of electrospinning is 9.5–10.5 kV, the negative voltage is -0.5–0 kV, and the precursor solution propulsion rate is 0.018–0.022 mL·min. -1 The distance between the spinning needle and the collector is 12-15 cm.

5. The method for preparing a porous carbon nanofiber microwave absorbing material with a nitrogen-cobalt-coordinated structure according to claim 1, characterized in that: In step 4, the pre-oxidation treatment temperature is 280 ℃, the holding time is 1–1.5 h, and the heating rate is 4–5 ℃·min. -1 Carbonization temperature: 700–900 ℃; holding time: 2–3 h; heating rate: 4–5 ℃·min. -1 .

Citation Information

Patent Citations

  • A method for preparing a cobalt-nickel alloy@nitrogen-doped porous carbon composite microwave absorbing material

    CN112266766B